Spatial differences in dissolved silicon utilisation in Lake Baikal, Siberia: examining the impact of high diatom biomass events and eutrophication - Panizzo, Virginia; Roberts, S.; Swann, George E.A.; McGowan, Suzanne; Mackay, Anson W.; Vologina, Elena; Pashley, Vanessa; Horstwood, Matthew S.A. (Wiley, 2018)
Recent research has highlighted how Lake Baikal, Siberia, has responded to the direct and indirect effects of climate change (e.g., ice-cover duration), nutrient loading, and pollution, manifesting as changes in phytoplankton/zooplankton populations, community structure, and seasonal succession. Here, we combine and compare= analyses of chlorophyll a (an estimate of total algal biomass), carotenoid pigments (biomarkers of algal groups), and lake water silicon isotope geochemistry (d30SiDSi) to differentiate spatial patterns in dissolved silicon (DSi) uptake at Lake Baikal. A total of 15 sites across the three basins (south, central, and north) of Lake Baikal were sampled in August 2013 along a depth gradient of 0–180 m. Strong, significant correlations were found between vertical profiles of photic zone DSi concentrations and d30SiDSi compositions (r 5 20.81, p < 0.001), although these are strongest in the central basin aphotic zone (r 5 20.98, p < 0.001). Data refute the hypothesis of DSi uptake by picocyanobacteria. Algal biomass profiles and high surface d30SiDSi compositions suggest greater productivity in the south basin and more oligotrophic conditions in the north basin. d30SiDSi signatures are highest at depth (20 m) in central basin sites, indicating greater (10–40%) DSi utilization at deep chlorophyll maxima. DSi limitation occurs in the pelagic central basin, probably reflecting a high diatom biomass bloom event (Aulacoseira baicalensis). Meanwhile in the more hydrologically restricted, shallow Maloe More region (central basin), both high d30SiDSi compositions and picocyanobacteria (zeaxanthin) concentrations, respectively point to the legacy of an “Aulacoseira bloom year” and continuous nutrient supply in summer months (e.g., localized eutrophication).